Pengembangan Media Video Powtoon Berorientasi Model PBL Pada Pembelajaran IPA Untuk Siwa Kelas V SD - Selpa Mai Ningsih; Yanti Fitria (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This research aims to develop a practical and valid media video learning with Powtoon video in Science learning for fifth grade students SDN 08 Minangkabau oriented to Problem Based Learning (PBL). This research is included as Research and Development (R&D) using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. This research is held on 2020/2021 academic year. Subjects of this research are three experts; material expert, media expert, and design expert, a fifth-grade teacher, and 16 fifth grade students. Instruments that are used in this research are expert validation sheet, teacher’s questionnaire sheet, and student’s questionnaire sheets. The result of this study shows that; 1) Media powtoon usage in Science learning oriented to Problem Based Learning (PBL) for fifth grade students SDN 08 Minangkabau is stated very valid by the experts with overall average score 92%, 2) Students and teacher’s responds result shows that Science learning with Powtoon media get average score 91,6% and 97,05%, both of them are categorized as very practical. As the result, it can be concluded that media video powtoon usage is very valid and practical in learning Science for fifth-grade elementary school students.